Research on green manufacturing technology. (July 2020) - Lin, Guomin; Hao, Botao
Abstract: The current situation, the contents and the features of green manufacturing technologies are introduced. The related technologies and the key technologies of green manufacturing technologies are analyzed. The contents, the targets and the carry out ways of green manufacturing technologies are researched. The development tendency and the application vistas of green manufacturing technologies are prospected.